Application of 1-phenylbiguanide hydrochloride to perovskite active layer, perovskite solar cell module and preparation methods of 1-phenylbiguanide hydrochloride and perovskite solar cell module
By introducing a small molecule modification layer of 1-phenylbiguanide hydrochloride in perovskite solar cells, the problem of surface defects of perovskite films is solved, and the photoelectric conversion efficiency and stability of solar cells are improved.
Patent Information
- Application Number
- CN202411496068.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-18
AI Technical Summary
The crystallization speed of FA/Cs-based perovskite in perovskite solar cells is fast, resulting in a large number of non-stable defects on the surface of the annealed film, resulting in non-radiative recombination of photogenerated carriers, reducing the photoelectric conversion efficiency and stability of solar cells. .
A small molecule modification layer, including 1-phenylbiguanide hydrochloride, is used to achieve passivation of surface defects by gradient mixing with the perovskite active layer. The preparation method includes spin coating perovskite precursor solution, dropping of antisolvent, one-step annealing, spin coating small molecule modification layer and two-step annealing to form a high-quality perovskite active layer.
It effectively reduces the energy loss of carriers at the interface, improves the open circuit voltage of the device, and improves the photoelectric conversion efficiency and stability.
Smart Images

Figure SMS_1 
Figure HDA0005101282000000011 
Figure HDA0005101282000000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite solar cells, and in particular relates to a method for preparing a solar cell active layer of small molecule doped methylammonium-free perovskite. Background Art
[0002] In just over a decade, perovskite solar photovoltaic devices have developed rapidly, and the current best certified efficiency is close to 27%, which is comparable to the performance of solar cells based on traditional photovoltaic materials such as copper indium gallium selenide, gallium arsenide and silicon. Among the many perovskite systems, FAPbI3 perovskite cells have a suitable band gap ( ~ 1.47eV), high absorption coefficient (greater than 104cm-1) and excellent carrier diffusion length (3.1μm), making it an important research hotspot and attracting widespread attention.
[0003] However, the large ionic radius of FA (0.19-0.22 nm) makes the thermodynamically stable α-phase FAPbI3 exist only under high temperature conditions (greater than 150°C), and it will spontaneously transform into the optically inactive δ-phase at room temperature. Therefore, people add Cs to this component to reduce its tolerance factor, thereby improving the room temperature stability of this perovskite phase. However, due to the fast crystallization rate of FA / Cs-based perovskites, there are a large number of non-stable defects on the surface of the annealed perovskite film. These defects will become carrier capture centers, causing a large number of photogenerated carriers to undergo non-radiative recombination at the interface, thereby generating voltage losses in photovoltaic devices and reducing the photoelectric conversion efficiency and stability of solar cells. Summary of the invention
[0004] In order to solve the problems raised in the above background technology, the present invention provides the following technical solution: a perovskite active layer, comprising a film of a gradient mixture of a perovskite active layer and a small molecule modification layer.
[0005] Furthermore, the small molecule modification layer includes 1-phenylbiguanide hydrochloride.
[0006] The method for preparing a perovskite active layer comprises the following steps:
[0007] Step 1: dissolving all components including formamidinium iodine, lead iodide and cesium iodide in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution;
[0008] Step 2: Spin coating the perovskite precursor solution;
[0009] Step 3: Add the anti-solvent to the surface of the perovskite film and continue spin coating;
[0010] Step 4: One-step annealing treatment to obtain the perovskite active layer.
[0011] Step 5: Drop 1-phenylbiguanidine hydrochloride onto the perovskite surface and spin coat.
[0012] Step 6: Two-step annealing treatment to obtain the final perovskite active layer.
[0013] Furthermore, in the step 1, the volume ratio of the mixed solution of deuterated dimethyl sulfoxide and dimethylformamide is 1:4;
[0014] The concentration of the perovskite precursor solution is 1.25 mol / L to 1.35 mol / L;
[0015] In the perovskite precursor solution,
[0016] The dosage of formamidinium iodine is 1.20 mol / L~1.28 mol / L;
[0017] The dosage of cesium iodide is 0.05mol / L~0.07mol / L;
[0018] The dosage of lead iodide is 1.355mol / L~1.375mol / L;
[0019] The dosage of amidinotaurine is 0.02mol / L~0.03mol / L;
[0020] The perovskite precursor solution spin-coated in step 2 is 30-40 μL;
[0021] The spin coating speed in step 2 is 3000 rpm to 5000 rpm;
[0022] The spin coating speed in step 3 is 3000 rpm to 5000 rpm;
[0023] The annealing conditions in step 4 are as follows: the annealing temperature is 100° C. to 200° C., and the annealing time is 5 min to 15 min;
[0024] The spin coating speed in step 5 is 1000 rpm to 3000 rpm;
[0025] The annealing conditions in step 6 are: annealing temperature 80-120° C., annealing time 3-8 min;
[0026] The anti-solvent is selected from chlorobenzene or ether.
[0027] Furthermore, the concentration of the perovskite precursor solution is 1.3 mol / L.
[0028] Furthermore, in the perovskite precursor solution, the amount of formamidinium iodide used is 1.235 mol / L.
[0029] Furthermore, in the perovskite precursor solution, the amount of cesium iodide used is 0.065 mol / L.
[0030] Furthermore, in the perovskite precursor solution, the amount of lead iodide used is 1.365 mol / L.
[0031] Furthermore, in the perovskite precursor solution, the amount of amidinotaurine used is 0.026 mol / L.
[0032] Furthermore, the spin coating speed in step 2 is 4500 rpm to 4500 rpm.
[0033] Furthermore, the spin coating speed in step 2 is 4000 rpm.
[0034] Furthermore, the perovskite precursor solution spin-coated in step 2 is 35 μL
[0035] Furthermore, the spin coating speed in step 3 is 4500 rpm to 4500 rpm.
[0036] Furthermore, the spin coating speed in step 3 is 4000 rpm.
[0037] Furthermore, the annealing temperature in step 4 is 80°C to 120°C.
[0038] Furthermore, the annealing temperature in step 4 is 100°C.
[0039] Furthermore, the annealing treatment time in step 4 is 8-13 minutes.
[0040] Furthermore, the annealing treatment time in step 4 is 10 minutes.
[0041] Furthermore, the spin coating speed in step 5 is 1500 rpm to 2500 rpm.
[0042] Furthermore, the spin coating speed in step 5 is 2000 rpm.
[0043] Furthermore, the annealing condition in step 6 is: annealing temperature 100°C.
[0044] Furthermore, the annealing treatment condition in step 6 is: the annealing treatment time is 5 minutes.
[0045] Perovskite solar cells include a conductive glass substrate, an electron transport layer, a perovskite film, a hole transport layer, a blocking layer and a metal electrode in sequence.
[0046] Furthermore, the conductive glass substrate is ITO glass;
[0047] The electron transport layer is tin oxide;
[0048] The small molecule modification layer is 1-phenylbiguanide hydrochloride;
[0049] The hole transport layer is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD);
[0050] The barrier layer is molybdenum oxide;
[0051] The metal electrode is gold or silver.
[0052] Furthermore, the metal electrode is silver.
[0053] Further,
[0054] The thickness of the electron transport layer is 1 to 100 nm;
[0055] The thickness of the small molecule modification layer is not less than 0.5 nm;
[0056] The thickness of the perovskite active layer is not less than 200 nm;
[0057] The thickness of the hole transport layer is 20 to 100 nm;
[0058] The thickness of the buffer layer is 3 to 20 nm;
[0059] The thickness of the metal electrode is 50 to 200 nm;
[0060] Furthermore, the thickness of the electron transport layer is 30-50 nm.
[0061] Furthermore, the thickness of the small molecule modification layer is not less than 1 to 3 nm;
[0062] Furthermore, the thickness of the perovskite film is 300-500 nm.
[0063] Furthermore, the thickness of the hole transport layer is 50-80 nm.
[0064] Furthermore, the thickness of the buffer layer is 5-8 nm.
[0065] Furthermore, the thickness of the metal electrode is 80-100 nm.
[0066] The preparation method of a perovskite solar cell comprises cleaning the surface of a conductive glass substrate, spin coating an electron transport layer, spin coating a perovskite film, spin coating a hole transport layer, evaporating a buffer layer, and evaporating a metal electrode, and is characterized in that it comprises the following steps:
[0067] Step 1: Clean the ITO substrate with a solvent and then dry it;
[0068] Step 2: Preparation of solution:
[0069] (a) Preparation of perovskite precursor solution:
[0070] In a protective gas atmosphere, lead halide, amine halide and cesium iodide are dissolved in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution;
[0071] (b) Preparation of 1-phenylbiguanide hydrochloride solution:
[0072] Preparation of 1-phenylbiguanide hydrochloride solution: 1 mg of 1-phenylbiguanide hydrochloride powder was thoroughly mixed with 1 mL of chlorobenzene solvent to obtain 1-phenylbiguanide hydrochloride solution;
[0073] (C) Preparation of hole transport layer solution:
[0074] Dissolving 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) in an organic solvent, chlorobenzene, to obtain a hole transport layer solution;
[0075] Step 3: Preparation of electron transport layer
[0076] In a protective gas atmosphere, the electron transport layer solution was spin-coated on the ITO substrate and annealed at 150°C for 20 min to obtain an ITO / ETL film;
[0077] Step 4: Preparation of perovskite active layer
[0078] In a protective gas atmosphere, the perovskite precursor solution is first spin-coated on the ITO / ETL film to start spin coating; then, 7 seconds before the end of spin coating, the anti-solvent chlorobenzene is dropped onto the film to continue spin coating; finally, annealing treatment is performed to obtain the perovskite active layer film;
[0079] Step 5: Preparation of small molecule modified layer
[0080] In a protective gas atmosphere, firstly spin-coating a 1-phenylbiguanide hydrochloride solution on the perovskite film to start spin coating; annealing treatment is performed to obtain a perovskite active layer film modified with small molecules;
[0081] Step 6: Preparation of hole transport layer
[0082] In a protective gas atmosphere, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) was spin-coated on the perovskite active layer;
[0083] Step 7, evaporating a barrier layer of molybdenum oxide;
[0084] Step 8: Evaporating metal electrodes.
[0085] Further,
[0086] The anti-solvent is chlorobenzene or ether, and the amount added in each spin coating is 60-80 μL;
[0087] The 1-phenylbiguanide hydrochloride solution is added dropwise in an amount of 80-120 μL each time;
[0088] The usage ratio of chlorobenzene solution and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) is 1 ml / 72 mg.
[0089] Furthermore, the anti-solvent is chlorobenzene or ethyl ether, and the amount added in each spin coating is 70 μL.
[0090] Furthermore, the 1-phenylbiguanide hydrochloride solution is added dropwise in an amount of 100 μL each time;
[0091] Further,
[0092] The protective gas is selected from nitrogen;
[0093] The ITO substrate dried in the step 1 is treated with vacuum ultraviolet ozone;
[0094] The spin coating speed in step 3 is 2000 rpm to 5000 rpm;
[0095] The spin coating speed in step 4 is 3000 rpm to 5000 rpm.
[0096] The annealing conditions in step 4 are as follows: the annealing temperature is 100°C to 200°C, and the annealing time is 5min to 15min;
[0097] The annealing conditions in step 5 are: annealing temperature 80°C to 150°C, annealing time 3min to 8min;
[0098] The evaporation conditions in step 5 are as follows: the pressure in the evaporation chamber is maintained at 2×10 -6 Below torr, evaporation at a rate of 0.01nm / s to 0.02nm / s;
[0099] The evaporation conditions in step 6 are as follows: the pressure in the evaporation chamber is maintained at 2×10 -6 Below torr, the deposition rate is 0.5nm / s to 1nm / s.
[0100] Furthermore, the spin coating speed in step three is 2500 rpm to 4000 rpm.
[0101] Furthermore, the spin coating speed in step three is 3000 rpm.
[0102] Furthermore, the spin coating speed in step 4 is 3500 rpm to 4500 rpm.
[0103] Furthermore, the spin coating speed in step 4 is 4000 rpm.
[0104] Furthermore, the annealing conditions in step 4 are as follows: the annealing temperature is 130°C to 180°C.
[0105] Furthermore, the annealing treatment condition in step 4 is: the annealing treatment temperature is 150°C.
[0106] Furthermore, the annealing treatment conditions in step 4 are: the annealing treatment time is 10 minutes.
[0107] Furthermore, the annealing treatment condition in step five is: annealing treatment temperature is 100°C.
[0108] Furthermore, the annealing treatment condition in step five is: the annealing treatment time is 5 minutes.
[0109] The beneficial effects of the present invention are:
[0110] 1. This technical solution introduces organic molecules to passivate the surface defects of the perovskite film, reducing the energy loss of carrier transmission at the interface, thereby increasing the device open circuit voltage and improving the device photovoltaic performance. The perovskite device prepared based on this has good photoelectric conversion efficiency and stability.
[0111] 2. This technical solution uses small molecule additives to improve the film quality of perovskite films, and is used to prepare efficient and stable perovskite solar cells. The organic small molecule material contains both electron-rich and electron-deficient functional groups. Based on the Lewis acid-base coordination theory, it can coordinate with various types of defects on the surface of the perovskite film, thereby achieving surface defect passivation. The modified layer can effectively inhibit the non-radiative recombination process of carriers, improve the transmission efficiency of photogenerated carriers at the perovskite interface, thereby reducing the voltage loss of perovskite photovoltaic devices, improving the photoelectric conversion efficiency, and improving the stability of the device; compared with unmodified perovskites, the surface defects of the perovskite film prepared by the method proposed in this technical solution are effectively passivated, the loss of photogenerated carriers at the interface due to non-radiative recombination is significantly suppressed, the open circuit voltage of the device is significantly improved, and the corresponding photoelectric conversion efficiency and stability are significantly improved.
[0112] 3. This technical solution proposes a strategy of introducing organic small molecules to modify the surface to improve the quality of perovskite films, that is, introducing 1-phenylbiguanidine hydrochloride organic molecules with both electron-rich and electron-deficient groups, and after a two-step annealing process, effectively passivating various defects on the perovskite surface.
[0113] 4. The operation steps of this technical solution are simple; the number of surface defects of the prepared perovskite film is small; the open circuit voltage of the photovoltaic device prepared based on the interface modified perovskite is significantly improved, and the photoelectric conversion efficiency and stability are significantly improved.
[0114] 5. This technical solution simplifies the preparation process and can be produced without adding additional hardware equipment. By improving the quality of perovskite films, the performance of corresponding devices is improved. It provides an effective strategy for preparing high-quality perovskite films. BRIEF DESCRIPTION OF THE DRAWINGS
[0115] Figure 1 This is a schematic structural diagram of a perovskite solar cell according to Example 1 of the present invention;
[0116] Figure 2 JV curves of perovskite solar cells modified with 1-phenylbiguanidine hydrochloride and unmodified;
[0117] Figure 3 The linear boost carrier extraction (Photo-CELIV) curves of perovskite solar cells with or without 1-phenylbiguanidine hydrochloride added;
[0118] Figure 4 The electroluminescence curves of the perovskite film with or without 1-phenylbiguanidine hydrochloride added;
[0119] Figure 5a Femtosecond transient absorption spectrum of perovskite film modified with 1-phenylbiguanide hydrochloride;
[0120] Figure 5b Femtosecond transient absorption spectrum of unmodified perovskite film;
[0121] Figure 6 The placement stability of photovoltaic devices prepared based on perovskite with or without 1-phenylbiguanidine hydrochloride added in a nitrogen environment at room temperature. DETAILED DESCRIPTION
[0122] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0123] See also Figure 1-6 The present invention provides the following technical solution: a perovskite active layer, comprising a film gradiently mixed with a perovskite active layer and a small molecule modified layer.
[0124] In this embodiment, the small molecule modification layer includes 1-phenylbiguanide hydrochloride.
[0125] In the above perovskite active layer, the small molecule modification layer is 1-phenylbiguanide hydrochloride, which is characterized by containing both electron-rich and electron-poor functional groups, and can serve as a potential passivation center; the perovskite has a chemical formula of ABX3, wherein A is a cation, including methylamine (CH3NH3 + ), formamidine (CH(NH2) 2+ or Cs + etc.; B is a divalent cation of a metal element of Group IV, including Pb 2+ Sn 2+ Or Ge 2+ etc.; X is a halogen ion or a halogen-like monovalent anion, including F - , Cl - Br - ,I - or SCN - wait.
[0126] The method for preparing a perovskite active layer comprises the following steps:
[0127] Step 1: dissolving all components including formamidinium iodine, lead iodide and cesium iodide in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution;
[0128] Step 2: Spin coating the perovskite precursor solution;
[0129] Step 3: Add the anti-solvent to the surface of the perovskite film and continue spin coating;
[0130] Step 4: One-step annealing treatment to obtain the perovskite active layer.
[0131] Step 5: Drop 1-phenylbiguanidine hydrochloride onto the perovskite surface and spin coat.
[0132] Step 6: Two-step annealing treatment to obtain the final perovskite active layer.
[0133] In this embodiment, for the unmodified perovskite film, only steps 5 and 6 need to be skipped, and the rest remain unchanged.
[0134] In this embodiment, the annealing treatment in step 6 may be performed by heating on a hot plate in a protective gas atmosphere.
[0135] In this embodiment, the volume ratio of the mixed solution of deuterated dimethyl sulfoxide and dimethylformamide in step 1 is 1:4;
[0136] The concentration of the perovskite precursor solution is 1.25 mol / L to 1.35 mol / L;
[0137] In the perovskite precursor solution,
[0138] The dosage of formamidinium iodine is 1.20 mol / L~1.28 mol / L;
[0139] The dosage of cesium iodide is 0.05mol / L~0.07mol / L;
[0140] The dosage of lead iodide is 1.355mol / L~1.375mol / L;
[0141] The dosage of amidinotaurine is 0.02mol / L~0.03mol / L;
[0142] The perovskite precursor solution spin-coated in step 2 is 30-40 μL;
[0143] The spin coating speed in step 2 is 3000 rpm to 5000 rpm;
[0144] The spin coating speed in step 3 is 3000 rpm to 5000 rpm;
[0145] The annealing conditions in step 4 are as follows: the annealing temperature is 100° C. to 200° C., and the annealing time is 5 min to 15 min;
[0146] The spin coating speed in step 5 is 1000 rpm to 3000 rpm;
[0147] The annealing conditions in step 6 are: annealing temperature 80-120° C., annealing time 3-8 min;
[0148] The anti-solvent is selected from chlorobenzene or ether.
[0149] In this embodiment, the concentration of the perovskite precursor solution is preferably 1.3 mol / L.
[0150] In this embodiment, preferably, the dosage of formamidinium iodine in the perovskite precursor solution is 1.235 mol / L.
[0151] In this embodiment, preferably, the amount of cesium iodide in the perovskite precursor solution is 0.065 mol / L.
[0152] Preferably, in this embodiment, the amount of lead iodide in the perovskite precursor solution is 1.365 mol / L.
[0153] In this embodiment, preferably, the amount of amidinotaurine in the perovskite precursor solution is 0.026 mol / L.
[0154] In this embodiment, the spin coating speed in step 2 is preferably 4500 rpm to 4500 rpm.
[0155] Preferably, in this embodiment, the spin coating speed in step 2 is 4000 rpm.
[0156] In this embodiment, the spin-coated perovskite precursor solution in step 2 is preferably 35 μL.
[0157] In this embodiment, the spin coating speed in step 3 is preferably 4500 rpm to 4500 rpm.
[0158] Preferably, in this embodiment, the spin coating speed in step 3 is 4000 rpm.
[0159] In this embodiment, preferably, the annealing temperature in step 4 is 80° C. to 120° C.
[0160] In this embodiment, preferably, the annealing temperature in step 4 is 100°C.
[0161] In this embodiment, preferably, the annealing treatment time in step 4 is 8-13 minutes.
[0162] Preferably, in this embodiment, the annealing treatment time in step 4 is 10 minutes.
[0163] In this embodiment, the spin coating speed in step 5 is preferably 1500 rpm to 2500 rpm.
[0164] Preferably, in this embodiment, the spin coating speed in step 5 is 2000 rpm.
[0165] In this embodiment, preferably, the annealing condition in step 6 is: annealing temperature 100°C.
[0166] In this embodiment, preferably, the annealing condition in step 6 is: the annealing time is 5 minutes.
[0167] Perovskite solar cells include a conductive glass substrate, an electron transport layer, a perovskite film, a hole transport layer, a blocking layer and a metal electrode in sequence.
[0168] In this embodiment, the conductive glass substrate is ITO glass;
[0169] The electron transport layer is tin oxide;
[0170] The small molecule modification layer is 1-phenylbiguanide hydrochloride;
[0171] The hole transport layer is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD);
[0172] The barrier layer is molybdenum oxide;
[0173] The metal electrode is gold or silver.
[0174] Preferably, in this embodiment, the metal electrode is silver.
[0175] In this embodiment,
[0176] The thickness of the electron transport layer is 1 to 100 nm;
[0177] The thickness of the small molecule modification layer is not less than 0.5 nm;
[0178] The thickness of the perovskite active layer is not less than 200 nm;
[0179] The thickness of the hole transport layer is 20 to 100 nm;
[0180] The thickness of the buffer layer is 3 to 20 nm;
[0181] The thickness of the metal electrode is 50 to 200 nm;
[0182] Preferably, in this embodiment, the thickness of the electron transport layer is 30-50 nm.
[0183] Preferably, in this embodiment, the thickness of the small molecule modification layer is not less than 1 to 3 nm;
[0184] Preferably, in this embodiment, the thickness of the perovskite film is 300-500 nm.
[0185] In this embodiment, preferably, the thickness of the hole transport layer is 50-80 nm.
[0186] Preferably, in this embodiment, the thickness of the buffer layer is 5-8 nm.
[0187] Preferably, in this embodiment, the thickness of the metal electrode is 80-100 nm.
[0188] The preparation method of a perovskite solar cell comprises cleaning the surface of a conductive glass substrate, spin coating an electron transport layer, spin coating a perovskite film, spin coating a hole transport layer, evaporating a buffer layer, and evaporating a metal electrode, and is characterized in that it comprises the following steps:
[0189] Step 1: Clean the ITO substrate with a solvent and then dry it;
[0190] Step 2: Preparation of solution:
[0191] (a) Preparation of perovskite precursor solution:
[0192] In a protective gas atmosphere, lead halide, amine halide and cesium iodide are dissolved in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution;
[0193] (b) Preparation of 1-phenylbiguanide hydrochloride solution:
[0194] Preparation of 1-phenylbiguanide hydrochloride solution: 1 mg of 1-phenylbiguanide hydrochloride powder was thoroughly mixed with 1 mL of chlorobenzene solvent to obtain 1-phenylbiguanide hydrochloride solution;
[0195] (C) Preparation of hole transport layer solution:
[0196] Dissolving 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) in an organic solvent, chlorobenzene, to obtain a hole transport layer solution;
[0197] Step 3: Preparation of electron transport layer
[0198] In a protective gas atmosphere, the electron transport layer solution was spin-coated on the ITO substrate and annealed at 150°C for 20 min to obtain an ITO / ETL film;
[0199] Step 4: Preparation of perovskite active layer
[0200] In a protective gas atmosphere, the perovskite precursor solution is first spin-coated on the ITO / ETL film to start spin coating; then, 7 seconds before the end of spin coating, the anti-solvent chlorobenzene is dropped onto the film to continue spin coating; finally, annealing treatment is performed to obtain the perovskite active layer film;
[0201] Step 5: Preparation of small molecule modified layer
[0202] In a protective gas atmosphere, firstly spin-coating a 1-phenylbiguanide hydrochloride solution on the perovskite film to start spin coating; annealing treatment is performed to obtain a perovskite active layer film modified with small molecules;
[0203] Step 6: Preparation of hole transport layer
[0204] In a protective gas atmosphere, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) was spin-coated on the perovskite active layer;
[0205] Step 7, evaporating a barrier layer of molybdenum oxide;
[0206] Step 8: Evaporating metal electrodes.
[0207] In this embodiment, the specific operation of cleaning the ITO substrate in step 1 is: ultrasonic cleaning is performed once with anhydrous isopropanol, deionized water, deionized water, deionized water and anhydrous isopropanol, each for 30 minutes; and then dried in a drying oven. Before use, the cleaned ITO glass needs to be treated with vacuum ultraviolet ozone (UV-Ozone). Ultraviolet ozone surface treatment can be achieved using equipment and processing conditions commonly used in the art, for example: UV-Ozone power is 200W, and the processing time is 3min.
[0208] In this embodiment,
[0209] The anti-solvent is chlorobenzene or ether, and the amount added in each spin coating is 60-80 μL;
[0210] The 1-phenylbiguanide hydrochloride solution is added dropwise in an amount of 80-120 μL each time;
[0211] The usage ratio of chlorobenzene solution and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) is 1 ml / 72 mg.
[0212] In this embodiment, the anti-solvent is preferably chlorobenzene or ethyl ether, and the amount added during each spin coating is 70 μL.
[0213] In this embodiment, the amount of the 1-phenylbiguanide hydrochloride solution added dropwise each time is 100 μL;
[0214] In this embodiment,
[0215] The protective gas is selected from nitrogen;
[0216] The ITO substrate dried in the step 1 is treated with vacuum ultraviolet ozone;
[0217] The spin coating speed in step 3 is 2000 rpm to 5000 rpm;
[0218] The spin coating speed in step 4 is 3000 rpm to 5000 rpm.
[0219] The annealing conditions in step 4 are as follows: the annealing temperature is 100°C to 200°C, and the annealing time is 5min to 15min;
[0220] The annealing conditions in step 5 are: annealing temperature 80°C to 150°C, annealing time 3min to 8min;
[0221] The evaporation conditions in step 5 are as follows: the pressure in the evaporation chamber is maintained at 2×10 -6 Below torr, evaporation at a rate of 0.01nm / s to 0.02nm / s;
[0222] The evaporation conditions in step 6 are as follows: the pressure in the evaporation chamber is maintained at 2×10 -6 Below torr, the deposition rate is 0.5nm / s to 1nm / s.
[0223] Preferably, in this embodiment, the spin coating speed in step three is 2500 rpm to 4000 rpm.
[0224] Preferably, in this embodiment, the spin coating speed in step three is 3000 rpm.
[0225] Preferably, in this embodiment, the spin coating speed in step 4 is 3500 rpm to 4500 rpm.
[0226] Preferably, in this embodiment, the spin coating speed in step 4 is 4000 rpm.
[0227] In this embodiment, preferably, the annealing conditions in step 4 are: the annealing temperature is 130° C. to 180° C.
[0228] In this embodiment, preferably, the annealing condition in step 4 is: the annealing temperature is 150°C.
[0229] Preferably, in the present embodiment, the annealing treatment condition in step 4 is: the annealing treatment time is 10 minutes.
[0230] In this embodiment, preferably, the annealing condition in step five is: annealing temperature is 100°C.
[0231] In this embodiment, preferably, the annealing condition in step five is: the annealing time is 5 minutes.
[0232] The test instruments and test conditions used in the examples are as follows:
[0233] JV curve: First, the light intensity of the solar simulator system is calibrated by the silicon photodiode and KG5 filter calibrated by the US Renewable Energy Laboratory. Then, the device is placed under the calibrated test light source using a test fixture (performed in an N2 glove box), and the JV characteristic curve of the perovskite semiconductor optoelectronic device is automatically tested by the Keithley source meter and the corresponding configured software, and the open-circuit voltage (V) is obtained from the curve. oc ), short-circuit current density (Short-circuit density, J sc), fill factor (FF) and power conversion efficiency (PCE).
[0234] During the JV curve test, the test voltage was set to -0.2V to 1.2V, the interval was 0.02V, and the delay time was 0.1s.
[0235] The electroluminescence efficiency of the devices was recorded using an optical test system (XPQY-EQE-350-1100, Guangzhou Xipu Optoelectronics Technology Co., Ltd.) equipped with a photodetector (S7031-1006, Hamamatsu Photonics) and an integrating sphere (GPS-4P-SL, Lapsphere).
[0236] Photo-CELIV was performed based on a commercially available PIAOs testing system (Fluxim4.0).
[0237] Unless otherwise stated, all solvents and materials used in the examples were obtained from commercial sources and used without further purification.
[0238] The ITO transparent electrode glass (10Ωsq -1 ) was purchased from Youxuan Technology Co., Ltd.
[0239] Cesium iodide (CsI, purity 99.999%), molybdenum oxide (MoO3, purity 99.97%), chlorobenzene (CB, purity 99.8%) were purchased from Sigma-Aldrich. Formamidinium iodide (FAI, purity ≥ 99.5%) and spiro-OMeTAD (purity ≥ 99.5%) were purchased from Xi'an Biolight Optoelectronics Technology Co., Ltd. 1-Phenylbiguanide hydrochloride (purity ≥ 99%) was purchased from Aladdin. PbI2 (purity 99.99%) was purchased from Tokyo Chemical Industry. DMSO (purity 99.9%) and DMF (purity ≥ 99%) were purchased from Acros Organics. SnO2 colloidal dispersion was purchased from AlfaAesar.
[0240] 1-Phenylbiguanidine hydrochloride modified group
[0241] The device structure of the perovskite solar cell in this modification group is: ITO / SnO2 / Perovskite / spiro-OMeTAD / MoO3 / Ag, such as Figure 1 shown.
[0242] Prepare electron transport layer solution:
[0243] A 15 mol / L tin oxide colloidal solvent was mixed with deionized water at a volume ratio of 1:3 to obtain a diluted tin oxide colloidal solution.
[0244] Preparation of perovskite solar cells (the experimental group and the control group have the same steps):
[0245] The ITO glass was ultrasonically cleaned in anhydrous isopropanol, deionized water, deionized water, deionized water and anhydrous isopropanol in turn, each for 30 minutes; then dried in a drying oven. Before using the cleaned ITO glass, its surface needs to be treated with vacuum ultraviolet ozone (UV-Ozone) for 3 minutes to improve wettability.
[0246] Spin-coat SnO2 colloidal dispersion to obtain SnO2 layer at 4000rpm for 30 seconds. Anneal the prepared glass / ITO / SnO2 / ZnO on a 150℃ hot plate for 20 minutes to promote complete evaporation of the solvent. After the annealing is completed and the substrate layer is cooled to room temperature, it is transferred to a nitrogen environment glove box, and then spin-coat the perovskite precursor solution to obtain the perovskite film at a speed of 4000rpm for 35 seconds. 8 seconds before the end of spin coating, quickly drop 70μL of chlorobenzene solution on the surface of the perovskite film. After the spin coating is completed, remove it and quickly anneal it on a 150℃ hot plate for 20 minutes. Drop the prepared 1-phenylbiguanide hydrochloride small molecule solution on the cooled perovskite film surface at a speed of 2000rpm for 30 seconds. Then spin-coat the prepared spiro-OMeTAD on the perovskite layer at a speed of 4000rpm for 20 seconds. Finally, the film was transferred to a high vacuum evaporation device and the vacuum degree was 2×10 -6 In a torr environment, MoO3 with a thickness of 7nm and Ag with a thickness of 100nm were sequentially evaporated.
[0247] The modified group, i.e., the control group, did not need to spin-coat the 1-phenylbiguanide hydrochloride small molecule solution, and the remaining steps were the same.
[0248] Current density voltage (JV) test
[0249] The current density voltage (JV) curve of the perovskite solar cells in the experimental group with 1-phenylbiguanidine hydrochloride added and the control group without 1-phenylbiguanidine hydrochloride added was tested. The results are shown in Figure 2 and Table 1.
[0250] Table 1. Photovoltaic parameters of devices in the experimental group and the control group
[0251]
[0252] from Figure 2As can be seen from Table 1, the short-circuit current density of the device with the introduction of phenyl biguanide hydrochloride small molecules increased from 23.82 to 24.43 mA / cm 2 , the open circuit voltage increased from 1.109 to 1.134V, and the fill factor increased from 73.59% to 80.52%. This result shows that the introduction of guanyl taurine can significantly suppress the defects inside the perovskite active layer to improve the carrier extraction efficiency and reduce the energy loss of the perovskite device. Finally, the photoelectric conversion efficiency of the perovskite solar cell increased from 19.44% to 22.31%.
[0253] according to Figure 2 It can be seen that the open circuit voltage (V OC ) and fill factor (FF) are significantly improved. The photoelectric conversion efficiency of the device modified with 1-phenylbiguanidine hydrochloride molecular layer is significantly higher than that of the unmodified device.
[0254] according to Figure 3 It can be seen that the photogenerated carrier density of the device modified with 1-phenylbiguanide hydrochloride is significantly larger, and the carrier extraction rate of the modified device is significantly improved compared with the unmodified device, indicating that 1-phenylbiguanide hydrochloride has a significant defect passivation effect on perovskite and effectively inhibits the non-radiative recombination of photogenerated carriers at the interface.
[0255] according to Figure 4 It can be seen that the electroluminescence intensity of the film modified with 1-phenylbiguanidine hydrochloride is significantly improved, indicating that most of the carriers in the perovskite undergo radiative recombination after modification, while the non-radiative recombination process of the carriers in the unmodified film is more obvious. This shows that 1-phenylbiguanidine hydrochloride has a good passivation effect on film defects.
[0256] Figure 5a and Figure 5b By comparing the femtosecond transient absorption spectra of the perovskite film modified with 1-phenylbiguanidine hydrochloride and without modification, it can be seen that both samples have obvious absorption peaks near the wavelength of 780nm, and no other stray peak signals are observed, indicating that the perovskite film is fully crystallized. However, the absorption peak of the perovskite film after the introduction of the modified layer is stronger, which reflects the better crystallinity of the film.
[0257] according to Figure 6 It can be seen that after 30 days of storage, the device modified with 1-phenylbiguanide hydrochloride can still maintain 97% of the initial efficiency, while the efficiency of the unmodified device drops to 75% of the initial efficiency. This shows that the modified device has better storage stability. This is because the interaction between the functional groups on the 1-phenylbiguanide hydrochloride molecules and the perovskite surface inhibits the phase separation of the perovskite film, thereby improving the phase stability of the perovskite.
[0258] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A perovskite active layer, characterized in that: It includes a film composed of a gradient mixture of a perovskite active layer and a small molecule modified layer.
2. The perovskite active layer according to claim 1, characterized in that: The small molecule modification layer includes 1-phenylbiguanide hydrochloride.
3. A method for preparing a perovskite active layer, characterized in that: The following steps are involved: Step 1: dissolving all components including formamidinium iodine, lead iodide and cesium iodide in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution; Step 2: Spin coating the perovskite precursor solution; Step 3: Add the anti-solvent to the surface of the perovskite film and continue spin coating; Step 4: One-step annealing treatment to obtain the perovskite active layer. Step 5: Drop 1-phenylbiguanidine hydrochloride onto the perovskite surface and spin coat. Step 6: Two-step annealing treatment to obtain the final perovskite active layer.
4. The method for preparing a perovskite active layer according to claim 1, characterized in that: The volume ratio of the mixed solution of deuterated dimethyl sulfoxide and dimethylformamide in step 1 is 1:4; The concentration of the perovskite precursor solution is 1.25 mol / L to 1.35 mol / L; In the perovskite precursor solution, The dosage of formamidine iodine is 1.20 mol / L to 1.28 mol / L; The dosage of cesium iodide is 0.05mol / L~0.07mol / L; The dosage of lead iodide is 1.355mol / L~1.375mol / L; The dosage of amidinotaurine is 0.02mol / L~0.03mol / L; The solvent is chlorobenzene; The perovskite precursor solution spin-coated in step 2 is 30-40 μL; The spin coating speed in step 2 is 3000 rpm to 5000 rpm; The spin coating speed in step 3 is 3000 rpm to 5000 rpm; The annealing conditions in step 4 are as follows: the annealing temperature is 100° C. to 200° C., and the annealing time is 5 min to 15 min; The spin coating speed in step 5 is 1000 rpm to 3000 rpm; The annealing conditions in step 6 are: annealing temperature 80-120° C., annealing time 3-8 min; The anti-solvent is selected from chlorobenzene or ether.
5. A perovskite solar cell, characterized in that: The method comprises, in sequence, a conductive glass substrate, an electron transport layer, a perovskite active layer according to any one of claims 1 to 2 or a perovskite active layer prepared by any one of claims 3 to 5, a hole transport layer, a barrier layer and a metal electrode.
6. The perovskite solar cell according to claim 5, characterized in that: The conductive glass substrate is ITO glass; The electron transport layer is tin oxide; The small molecule modification layer is 1-phenylbiguanide hydrochloride; The hole transport layer is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD); The barrier layer is molybdenum oxide; The metal electrode is gold or silver.
7. The perovskite solar cell according to claim 6, characterized in that: The thickness of the electron transport layer is 1 to 100 nm; The thickness of the perovskite active layer is not less than 200 nm; The thickness of the small molecule modification layer is not less than 0.5 nm; The thickness of the hole transport layer is 20 to 100 nm; The thickness of the buffer layer is 3 to 20 nm; The thickness of the metal electrode is 50-200 nm.
8. A method for preparing a perovskite solar cell, comprising cleaning the surface of a conductive glass substrate, spin coating an electron transport layer, spin coating a perovskite film, spin coating a hole transport layer, evaporating a buffer layer, and evaporating a metal electrode, characterized in that: The following steps are involved: Step 1: Clean the ITO substrate with a solvent and then dry it; Step 2: Preparation of solution: (a) Preparation of perovskite precursor solution: In a protective gas atmosphere, lead halide, amine halide and cesium iodide are dissolved in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution; (b) Preparation of 1-phenylbiguanide hydrochloride solution: Preparation of 1-phenylbiguanide hydrochloride solution: 1 mg of 1-phenylbiguanide hydrochloride powder was thoroughly mixed with 1 mL of chlorobenzene solvent to obtain 1-phenylbiguanide hydrochloride solution; (C) Preparation of hole transport layer solution: Dissolving 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) in an organic solvent, chlorobenzene, to obtain a hole transport layer solution; Step 3: Preparation of electron transport layer In a protective gas atmosphere, the electron transport layer solution was spin-coated on the ITO substrate and annealed at 150°C for 20 min to obtain an ITO / ETL film; Step 4: Preparation of perovskite active layer In a protective gas atmosphere, the perovskite precursor solution is first spin-coated on the ITO / ETL film to start spin coating; then, 7 seconds before the end of spin coating, the anti-solvent chlorobenzene is dropped onto the film to continue spin coating; finally, annealing treatment is performed to obtain the perovskite active layer film; Step 5: Preparation of small molecule modified layer In a protective gas atmosphere, firstly spin-coating a 1-phenylbiguanide hydrochloride solution on the perovskite film to start spin coating; annealing treatment is performed to obtain a perovskite active layer film modified with small molecules; Step 6: Preparation of hole transport layer In a protective gas atmosphere, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) was spin-coated on the perovskite active layer; Step 7, evaporating a barrier layer of molybdenum oxide; Step 8: Evaporating metal electrodes.
9. The method for preparing a perovskite solar cell according to claim 8, characterized in that: The anti-solvent is chlorobenzene or ether, and the amount added in each spin coating is 60-80 μL; The 1-phenylbiguanide hydrochloride solution is added dropwise in an amount of 80-120 μL each time; The usage ratio of chlorobenzene solution and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) is 1 ml / 72 mg.
10. The method for preparing a perovskite solar cell according to claim 8, characterized in that: The protective gas is selected from nitrogen; The ITO substrate dried in the step 1 is treated with vacuum ultraviolet ozone; The spin coating speed in step 3 is 2000 rpm to 5000 rpm; The spin coating speed in step 4 is 3000 rpm to 5000 rpm; 4000 rpm The annealing conditions in step 4 are: annealing temperature of 100°C to 200°C, annealing time of 5min to 15min; annealing temperature of 150°C, annealing time of 10min; The spin coating speed in step 5 is 1000-3000 rpm; The annealing conditions in step 5 are: annealing temperature 80°C to 150°C, annealing time 3min to 8min; annealing temperature 100°C, annealing time 5min The evaporation conditions of step 57 are as follows: the pressure of the evaporation chamber is maintained at 2×10 -6 Below torr, evaporation at a rate of 0.01nm / s to 0.02nm / s; The evaporation conditions in step eight are as follows: the pressure in the evaporation chamber is maintained at 2×10 -6 Below torr, the deposition rate is 0.5nm / s to 1nm / s.
Citation Information
Cited By
Biguanide molecule modified wide-band gap perovskite solar cell and preparation method thereof
CN121099822A